Design, Synthesis, in Vitro, and in Silico Evaluation of N‐Phenylacetamide‐Oxindole‐Thiosemicarbazide Hybrids as New Potential Tyrosinase Inhibitors. Issue 4 (8th March 2022) - Yari Boroujeni, Shahriar; Haghighijoo, Zahra; Mohammadi‐Khanaposhtani, Maryam; Mosadeghkhah, Ali; Moazzam, Ali; Yavari, Ali; Hajimahmoodi, Manan; Sabourian, Reyhaneh; Hosseini, Samesadat; Larijani, Bagher; Hamedifar, Halleh; Ansari, Samira; et al.
Abstract: A novel series of N ‐phenylacetamide‐oxindole‐thiosemicarbazide hybrids were synthesized and evaluated for their tyrosinase inhibitory activity. According to tyrosinase inhibition results, all the synthesized compounds showed high tyrosinase inhibitory activity with IC50 values ranging from 0.8 to 3.88 μM in comparison to positive control kojic acid with IC50 value of 36.32 μM. Among tested compounds, analog 7o, containing the 2‐methyl‐4‐nitrophenyl on N ‐phenylacetamide moiety displayed superior tyrosinase inhibition. This compound was around 45‐fold more potent than kojic acid. The kinetic analysis of compound 7o demonstrated that this compound is a competitive inhibitor against tyrosinase. Docking study of this compound demonstrated that compound 7o interacted with critical histidine residues within tyrosinase active site. Abstract :